EFFECTIVENESS OF BASIC MATHEMATICS TEACHING MATERIALS STUDY PROGRAM IN INFORMATICS ENGINEERING EDUCATION - Lili Rismaini; Dewi Devita; Syelfia Dewimarni (Jurnal Ilmu Pendidikan Ahlussunnah, 2022)
Background of this research is based on the difficulty of students understanding the material and knowledge of terms in mathematics that are less familiar in their learning environment so that with the development of this teaching material, it is hoped that student learning outcomes will be more optimal. This study aims to produce basic mathematics teaching materials that are valid and effective in basic mathematics learning. The type of this research is development research with the chosen development model, namely the Smith and Ragan model. This research was carried out on students of the informatics engineering education study program at the University of Putra Indonesia "YPTK" Padang. The research instrument was developed to assess the validity and effectiveness of basic mathematics teaching materials. The conclusion of this study is that at the validity stage of obtaining an average of 87.17% with very valid criteria, at the effectiveness stage using statistical analysis, namely the Paired Sample Test equation with a sig (2-tailed) result of 0.000 < an alpha value of 0.05 meaning that the value of Sig.2 tailed (0.000) is small from the alpha value ( 0.05) so it can be concluded that Ho is rejected and Hi is accepted, meaning that there is a significant difference between students' mathematics learning outcomes before and after using basic mathematics teaching materials.